A thermocouple-based remote temperature controller of an electrically-floated sample for plasma CVD of nanocarbons with bias voltage. (May 2017) - Shimada, Toshihiro; Miura, Takuya; Xie, Wei; Yanase, Takashi; Nagahama, Taro
Graphical abstract: Highlights: Accurate measurement of temperature by a thermocouple in plasma and for electrically floating sample is provided. Protection circuits to prevent the damage by surge in plasma are designed. Growth of nanocarbons by plasma CVD was studied using the accurate temperature measurement. Abstract: We report an accurate and easy-to operate instrument for the temperature control of an electrically-floated sample using a thermocouple in direct contact with it. The signal was transmitted via 2.45 GHz WiFi. We measured and analyzed the discrepancy between the thermocouple and a radiation thermometer for the plasma CVD of carbon nanomaterials under sample bias. A successful protection method from abnormal discharge in the plasma is also provided.